Interpretative phenomenological analysis : theory, method and research - Smith, Jonathan A.; Larkin, Michael Howard; Flowers, Paul. (Los Angeles ; London : SAGE, 2009)
Interpretative phenomenological analysis (IPA) is an increasingly popular approach to qualitative inquiry. This handy text covers its theoretical foundations and provides a detailed guide to conducting IPA research. Extended worked examples from the authors' own studies in health, sexuality, psychological distress and identity illustrate the breadth and depth of IPA research. Each of the chapters also offers a guide to other good exemplars of IPA research in the designated area. The final section of the book considers how IPA connects with other contemporary qualitative approaches like discourse and narrative analysis and how it addresses issues to do with validity. The book is written in an accessible style and will be extremely useful to students and researchers in psychology and related disciplines in the health and social sciences. -- Publisher's website.
Includes bibliograhical references and index.
Keywords: Phenomenological psychology; Psychology -- Research